Analisis Buku Teks Kimia Sekolah Menengah Atas (SMA) Negeri Kelas XI Berdasarkan Indikator Literasi Sains - Septia Marisa; Dedi Irwandi; Buchori Muslim (LPPM Universitas Negeri Jakarta, 2020)
One of the factors directly related to learning activities that affects the level of students' scientific literacy is the use of textbooks. Given the importance of mastering the ability of scientific literacy by students, the learning process of students needs to be supported by the use of textbooks that are able to provide science literacy content. The purpose of this research to know the science literacy level on chemistry textbook for 11th grade XI based on indicators of science literacy. The indicators are knowledge of science, investigative nature of science, science as the way of thinking, and interaction among science, technology and society. The method used in this research is descriptive method. The analyzed books were books that used in State Senior High School in Bogor country. The instruments used is observation sheet containing an analysis table of science literacy indicators. The result of the research is showed the level of science literacy that apperas is 45,51% for knowledge of science indicator, 41,03% for investigative nature of science indicator, 8,33% for science as the way of thinking indicator, and 5,13% for interaction among science, technology and society indicator. From the result, it can be conclude that, generally, the chemistry textbook for 11th grade State Senior High School that analyzed more present knowledge of science and less present science as the way of thinking. Keywords Analysis, chemistry textbook, science literacy